Analysis of the Influence of Brand Association, Brand Image, Brand Awareness, and Brand Loyalty on Brand Equity of Telon Oil - Indrayana, Rony; Faizatun; Derriawan (GoAcademica Research & Publishing, 2024)
This research aims to analyze the influence of brand association, brand image, brand awareness, and brand loyalty on brand equity of telon oil. This research uses a quantitative approach with the sample in the study being women or men aged 25 – 55 years and who have used My Baby telon oil. In carrying out this research, researchers used data analysis methods using the Likert scale measurement method, questionnaire data analysis using the SPSS 26 statistical program with the SEM SmartPLS method. The research results show several important findings regarding the relationship between the main variables in the context of Brand Equity. First, Brand Association (X1) significantly influences Brand Equity (Z) and Brand Loyalty (Y). Second, Brand Awareness (X2) has a significant influence on Brand Loyalty (Y), but not on Brand Equity (Z). Third, Brand Image (X3) significantly influences Brand Equity (Z), but not significantly on Brand Loyalty (Y). Apart from that, Brand Loyalty (Y) was also found to have a significant influence on Brand Equity (Z). These findings provide important insights for marketing and brand management strategies to strengthen key aspects that influence consumer perception and loyalty towards brands.